Novel protective role of the circadian nuclear receptor retinoic acid‐related orphan receptor‐α in diabetic cardiomyopathy. Issue 3 (22nd February 2017) - Zhao, Yichao; Xu, Longwei; Ding, Song; Lin, Nan; Ji, Qingqi; Gao, Lingchen; Su, Yuanyuan; He, Ben; Pu, Jun
Abstract: Diabetic cardiomyopathy is a major complication that significantly contributes to morbidity and mortality in diabetics with few therapies. Moreover, antidiabetic drugs reported inconsistent or even adverse cardiovascular effects, suggesting that it is important to exploit novel therapeutic targets against diabetic cardiomyopathy. Here, we observed that the nuclear melatonin receptor, the retinoic acid‐related orphan receptor‐α (RORα), was downregulated in diabetic hearts. By utilizing a mouse line with RORα disruption, we demonstrated that RORα deficiency led to significantly augmented diastolic dysfunction and cardiac remodeling induced by diabetes. Microscopic and molecular analyses further indicated that the detrimental effects of RORα deficiency were associated with aggravated myocardial apoptosis, autophagy dysfunction, and oxidative stress by disrupting antioxidant gene expression. By contrast, restoration of cardiac RORα levels in transgenic mice significantly improved cardiac functional and structural parameters at 8 weeks after diabetes induction. Consistent with genetic manipulation, pharmacological activation of RORα by melatonin and SR1078 (a synthetic agonist) showed beneficial effects against diabetic cardiomyopathy, while the RORα inhibitor SR3335 significantly exacerbated cardiac impairments in diabetic mice. Collectively, these findings suggest that cardiac‐targeted manipulation of nuclear melatonin receptor RORα may hold promise for delaying diabetic cardiomyopathy development.